2023
DOI: 10.3390/s23115038
|View full text |Cite
|
Sign up to set email alerts
|

Contactless Technologies, Sensors, and Systems for Cardiac and Respiratory Measurement during Sleep: A Systematic Review

Abstract: Sleep is essential to physical and mental health. However, the traditional approach to sleep analysis—polysomnography (PSG)—is intrusive and expensive. Therefore, there is great interest in the development of non-contact, non-invasive, and non-intrusive sleep monitoring systems and technologies that can reliably and accurately measure cardiorespiratory parameters with minimal impact on the patient. This has led to the development of other relevant approaches, which are characterised, for example, by the fact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Indeed, we have previously evaluated the CSTs against sleep diary-assisted actigraphy and have shown that the CSTs provide reliable estimates of bed occupancy in older people living at home [22]. Given their multimodal capabilities, improvements to their sleep detection algorithms to generalize results across populations could potentially lead to reliable sleep measures on par with PSG in the near future [8,37].…”
Section: Overviewmentioning
confidence: 99%
“…Indeed, we have previously evaluated the CSTs against sleep diary-assisted actigraphy and have shown that the CSTs provide reliable estimates of bed occupancy in older people living at home [22]. Given their multimodal capabilities, improvements to their sleep detection algorithms to generalize results across populations could potentially lead to reliable sleep measures on par with PSG in the near future [8,37].…”
Section: Overviewmentioning
confidence: 99%
“…At 1 minute resolution, the under-mattress devices had an acceptable accuracy with MAE < 2.12 bpm and MAPE < 5 % for heart rate estimate which is lower than the errors reported in the literature for wearable technologies during daily activities and for many contactless technologies during sleep [24, 28]. The breathing rate estimates at 1 minute resolution were acceptable across all three devices with a MAE ≤ 1.6 cpm and MAPE > 12 % and was comparable to other contactless technologies in in previous evaluations in young participants [28].…”
Section: Discussionmentioning
confidence: 95%
“…At 1 minute resolution, the under-mattress devices had an acceptable accuracy with MAE < 2.12 bpm and MAPE < 5 % for heart rate estimate which is lower than the errors reported in the literature for wearable technologies during daily activities and for many contactless technologies during sleep [24, 28]. The breathing rate estimates at 1 minute resolution were acceptable across all three devices with a MAE ≤ 1.6 cpm and MAPE > 12 % and was comparable to other contactless technologies in in previous evaluations in young participants [28]. The accuracy of both the vital signs estimates was higher during sleep than wake primarily due to reduced body movements.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The public realization of the importance of this individualized mental health continuum is reflected in the surge of personal health monitoring devices and biosensors in recent years (Kulkarni et al, 2022;Boiko et al, 2023;Seiferth et al, 2023). Managing mental wellness has been further ignited by the burdens of the COVID-19 pandemic, which increased the reported cases of anxiety and depression across different age groups and brought new concerns regarding its long-term consequences on mental health and performance (Leung et al, 2022;Zeng et al, 2023).…”
mentioning
confidence: 99%